2023
DOI: 10.1111/modl.12866
|View full text |Cite
|
Sign up to set email alerts
|

Use of word lists in a high‐stakes, low‐exposure context: Topic‐driven or frequency‐informed

Emma Marsden,
Amber Dudley,
Rachel Hawkes

Abstract: The awarding organizations that create and administer high‐stakes assessments for beginner‐to‐low‐intermediate 16‐year‐old learners of French, German, and Spanish in England provide optional topic‐driven word lists as guides for teachers and textbook writers. Given that these lists are developed by the awarding organizations, they exert a powerful washback effect on teaching and learning. However, we do not know how much of these lists have actually been used in exams. We therefore analyzed the extent to which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…Clearly, other factors, such as "semantic neutrality, length, part of speech, polysemy, morphological regularity, cognateness, [and] orthographic transparency" (Hashimoto, 2021, p. 182), also influence lexical difficulty, and the difficulty of any written or spoken text involves many dimensions beyond the lexicon. Similarly, objective word frequency information (e.g., corpus-based data and lexical coverage) should not be the sole criterion for wordlist development, which can helpfully also draw on subjective criteria (e.g., teacher evaluations; Dang et al, 2020;He & Godfroid, 2019;Marsden et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, other factors, such as "semantic neutrality, length, part of speech, polysemy, morphological regularity, cognateness, [and] orthographic transparency" (Hashimoto, 2021, p. 182), also influence lexical difficulty, and the difficulty of any written or spoken text involves many dimensions beyond the lexicon. Similarly, objective word frequency information (e.g., corpus-based data and lexical coverage) should not be the sole criterion for wordlist development, which can helpfully also draw on subjective criteria (e.g., teacher evaluations; Dang et al, 2020;He & Godfroid, 2019;Marsden et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, other factors, such as "semantic neutrality, length, part of speech, polysemy, morphological regularity, cognateness, [and] orthographic transparency" (Hashimoto, 2021, p. 182), also influence lexical difficulty, and the difficulty of any written or spoken text involves many dimensions beyond the lexicon. Similarly, objective word frequency information (e.g., corpus-based data and lexical coverage) should not be the sole criterion for wordlist development, which can helpfully also draw on subjective criteria (e.g., teacher evaluations; Dang et al, 2020;He & Godfroid, 2019;Marsden et al, 2023). Assuming that it is not possible to substantially increase curriculum time given to French, German, or Spanish, then more clearly defining the lexical content for GCSE exams, with a higher concentration of high-frequency words, could help tighten the link between 'what is taught' and 'what can be assessed' and allow students to get more return for their learning effort (Laufer & Nation, 2012;Nation, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, much of this vocabulary is likely to be mid-to-low frequency: Marsden, Dudley, and Hawkes (2023), for instance, reported that of the 1,322 flemmas on AQA's (the leading awarding organisation in England) current GCSE French wordlist, only 48% were highfrequency. Thus, any test of vocabulary knowledge that randomly samples 20 or even 30 words from each band is unlikely to provide a valid or useful measure of these students' vocabulary knowledge.…”
Section: Limitations Of Existing Testsmentioning
confidence: 99%